N-Methyl D-aspartate receptor subtype 2B/Ca2+/calmodulin-dependent protein kinase II signaling in the lateral habenula regulates orofacial allodynia and anxiety-like behaviors in a mouse model of trigeminal neuralgia - Zhuang, Zi-Fan; Wu, Hong-Yun; Song, Ya-Yi; Li, Lei; Cui, Xia; Yang, Jie; Xu, Xiang-Qing; Cui, Wen-Qiang (Frontiers in Cellular Neuroscience, 2022)
Trigeminal neuralgia (TN) is a peripheral nerve disorder often accompanied by abnormalities in mood. The lateral habenula (LHb) plays important roles in the modulation of pain and emotion. In the present study, we investigated the involvement of the LHb in the mechanisms underlying allodynia and anxiety induced by partial transection of the infraorbital nerve (pT-ION) in mice. Our results indicated that pT-ION induced persistent orofacial allodynia and anxiety-like behaviors, which were correlated with increased phosphorylation of N-Methyl D-aspartate receptor (NMDAR) subtype 2B (p-NR2B) and Ca2+/calmodulin-dependent protein kinase II (p-CaMKII) in LHb neurons. Bilateral inhibition of NMDARs and CaMKII in the LHb attenuated the allodynia and anxiety-like behavior induced by pT-ION. Furthermore, bilateral activation of NMDARs in the LHb increased the expression of p-NR2B and p-CaMKII and induced orofacial allodynia and anxiety-like behaviors in naive mice. Adeno-associated virus (AAV)-mediated expression of hM3D(Gq) in CaMKII+ neurons of the bilateral LHb, followed by clozapine-N-oxide (CNO) administration, also triggered orofacial allodynia and anxiety-like behaviors in naïve mice with successful virus infection in LHb neurons (verified based on immunofluorescence). In conclusion, these findings suggest that activation of NMDA/CaMKII signaling in the LHb contributes to the occurrence and development of TN and related anxiety-like behaviors. Therefore, suppressing the activity of CaMKII+ neurons in the bilateral LHb by targeting NMDA/CaMKII may represent a novel strategy for treating pain and anxiety associated with TN.